The Arctic Ocean Manganese Cycle, an Overlooked Mechanism in the Anomalous Palaeomagnetic Sedimentary Record - Wiers, Steffen; Snowball, Ian; O’Regan, Matt; Pearce, Christof; Almqvist, Bjarne (Frontiers in Earth Science, 2020)
Palaeomagnetic records obtained from Arctic Ocean sediments are controversial because they include numerous and anomalous geomagnetic excursions. Age models that do not rely on palaeomagnetic interpretations reveal that the majority of the changes in inclination do not concur with the established global magnetostratigraphy. Seafloor oxidation of (titano)magnetite to (titano)maghemite with self-reversal of the (titano)maghemite coatings has been proposed as an explanation. However, no existing model can explain when the self-reversed components formed and how they are linked to litho-stratigraphic changes in Arctic Ocean sediments. In this study, we present new palaeo- and rock magnetic measurements of a sediment core recovered from the Arlis Plateau, close to the East Siberian Shelf. The magnetic data set is evaluated in the context of the regional stratigraphy and downcore physical and chemical changes. By cross-core correlation, we show that magnetic inclination changes in the region are not stratigraphically aligned, similar to studies of sediments from the Lomonosov Ridge and Yermak Plateau. Rock magnetic and chemical parameters indicate post-depositional diagenetic changes in the magnetic mineral assemblage that can be linked to manganese cycling in the Arctic Ocean. The potential presence of a magnetic remanence bearing manganese-iron oxide phase, which can undergo self-reversal, leads to an alternative hypothesis to primary seafloor oxidation of (titano)magnetite. This phase may form by precipitation from seawater or by changing redox conditions in the sediment column by mineral precipitation from ions dissolved in pore water. These findings highlight the need for further investigation into the magnetic mineral assemblage, its link to manganese cycling and pore water geochemistry in Arctic Ocean sediments.